Ethics, morality and medical writing - NEHMÉ, Edgard (International Arab Journal of Dentistry (IAJD), 2013)
“The purpose of all morality is to consider human life as a part that can win or lose and teach men the way to win.” For moral of ambiguity, Simone de Beauvoir